Perilaku Ibu dalam Memilih Tenaga Penolong Persalinan di Wilayah Kerja Puskesmas Tembilahan Hulu Tahun 2016 - Alhidayati Alhidayati; Asmuliyanti Asmuliyanti (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Maternal Mortality Rate (MMR) is an indicator of health development in Indonesia. Some effort have been done to decrease maternal mortality ie to increase range labor by health personnel. The target coverage of labor by health personnel in Tembilahan Hulu Public health center has yet to reach the target of 80%. its coverage was only 45%. The number of maternal mortality in Tembilahan Hulu Health center in 2016 was 1 cases and the number of infant maternal mortality was 5 cases.Objective: The purpose of this study was to determine the mother’s behavior in selecting birth attendants in health center in the region of the upstream Tembilahan Hulu.Method: This research used qualitative method to gain the in depth information on how to Mother’s Behavior In Selecting Birth Attendants In Health Centers Working Area Tembilahan Hulu 2016. The data are analysed by using content analysis, which is comparing the result from the research with the theories in the literature.Result and Discussion: There were 13 informants in this research. This study’s result showed that the decision for birth attendants were closely related to knowledge, attitude, socio-cultural, access to health center, and support from family. Advise to relevant agencies, namely health centers Tembilahan Hulu order to further increase coverage deliveries by health care and in personels villages to which access is far from health facilities to build Birth Waiting Homes (BWH).Conclusion: The Decision for birth attendants were closely related to knowledge, attitude, socio cultural, acces to health center and support from family.Keywords: birth attendant, community health center, pregnant women behavior